Crossing the River Styx : the memoir of a death row chaplain - Ford, Russ, 1951- (University of Virginia Press, 2023)
"The memoir of Russ Ford, a former Virginia prison chaplain who by the time he retired had accompanied twenty-eight men into the death chamber. Drawing on the stories of the condemned men, and his relationship with them, Ford illuminates the brutality of and myriad problems with capital punishment"--